EFFICACY OF DIFFERENT DOSAGE REGIMENS OF CARBIMAZOLE IN THE TREATMENT OF PRIMARY HYPERTHYROIDISM - Usman, Rashid; Ismail, Shafaq; Tahir, Rimsha; Jamil, Muhammad (Journal of Ayub Medical College Abbottabad, 2021)
Background: Carbimazole is a prodrug that is converted to methimazole as soon as it is taken orally (15-30 minutes required). The plasma half-life of carbimazole is 5.3-5.4 hours, while that of its active counterpart, methimazole, is 64 hours. However, in the thyroid gland its half-life is up to 20 hours prompting to the sufficiency of a single dose of its pro drug carbimazole in hyperthyroid patients. Objectives were to compare the efficacy of Single dose with Divided dose regimen of Carbimazole for the induction of Euthyroidism in hyperthyroid patients. Methods: All consecutive hyperthyroidism patients from December 2018 to December 2019 fulfilling the inclusion criteria were included. They were allocated randomly into 2 groups: Group A - single dose of Carbimazole (OD-CMZ) and Group B - divided dose of Carbimazole (DD-CMZ). The therapeutic efficacy was measured at regular intervals (every 4 weeks) for 6 months. Their demographics and therapeutic management were analysed. Results: Of a total of 69 (n=34 in Group A, n=35 in Group B) patients, there was no significant difference in baseline concentrations of TSH and T4 as well as their cumulative rate of reductions (p value, 0.023). Furthermore, no difference in achieving euthyroidism was noted at follow-up visits between Group A and B respectively ([0:0%; p value 1.00, month 1], [70.6:74.3%; p value 0.22, month 2], [85.3:85.7%; p value 0.39, month 3], 97.1:82.9%; p value 0.23, month 4], [100:91.4%; p value 0.29, month 5], [100:100%%; p value 1.00, month 6] at monthly intervals. Cases of Hypothyroidism were reported more in the DD-CMZ (14.3%) and the difference was statistically significant (p value 0.003). Conclusion: Due to no significant difference in the efficacy and more chances of getting hypothyroid in divided dose regimen, we conclude that single dose regimen is more effective method for treating hyperthyroidism.